Science citizen: shifting to a “science-first” approach and recognising the trade-offs between objectives in a long-term citizen science program - O’Reilly, Woo; Starrs, Danswell (Frontiers in Environmental Science, 2023)
Citizen science is a powerful force for scientific enquiry, allowing volunteers to collect data over broader spatial and temporal scales than could be achieved using traditional methods. Many citizen science programs, however, have suffered from a lack of confidence in the data due to a range of both real and perceived issues, resulting in low recognition and a lack of data uptake by researchers and policy makers. This in turn can threaten the very existence of citizen science programs that are dependent on external funding. In this paper, we explore the shift to a 'data-first' approach undertaken by a long-term citizen science program, Upper Murrumbidgee Waterwatch. The 'data-first' approach has enabled Upper Murrumbidgee Waterwatch to better partition and appropriately manage the program's key areas of data collection, education and awareness raising. Moving towards a contributory typology, whilst recognising the positive elements that come with the original collaborative model, has enabled more strategic data collection and better data quality. This has resulted in greater data uptake in catchment management decision-making as well as secure, longterm funding for the program.